Why do bad balls get wickets? The role of congruent and incongruent information in anticipation - Runswick, O. R.; Roca, A.; Williams, A. M.; McRobert, A. P.; North, J. S. (Journal of Sports Sciences, 2019)
Skilled anticipation is underpinned by the use of kinematic and contextual information. However, few researchers have examined what happens when contextual information suggests an outcome that is different from the event that follows. We aimed to bridge this gap by manipulating the relationship between contextual information and final ball location in a cricket-batting task. We predicted that when contextual information is congruent with the eventual outcome then anticipation would be facilitated. In contrast, when contextual information is incongruent, this would lead to a confirmation bias on kinematic information and result in decreased anticipation accuracy. We expected this effect to be larger in skilled performers who are more able to utilise context. Skilled and less-skilled cricket batters anticipated deliveries presented using a temporally occluded video-based task. We created conditions whereby contextual information and event outcome were either congruent or incongruent. There was a significant skill by condition interaction (p < 0.05). The skilled group anticipated significantly more accurately than the less-skilled group on the congruent trials. Both groups anticipated less accurately on incongruent trials, with the skilled participants being more negatively affected. Skilled performers prioritise contextual information and confirmation bias affects the use of kinematic information available later in the action.